Uso de ultrassom na síntese de diacilglicerol via hidrólise enzimática de óleo de girassol - Raizer, Eduardo (2015)
Oils and fats are essential foods to the human diet, nevertheless, the negative impact caused by its overconsumption is of great concern worldwide. Diacylglycerol rich oils have orga- noleptic features very similar to those found in conventional edible oils, however, these oils do not tend to accumulate on the body, even when consumed in high quantities, becoming a great resource in the fight against obesity. Sunflower oil is among the most consumed edible oils in the world, and also, is naturally one of the healthiest. This study s goal was to evalu- ate the influence of ultrasound on the enzymatic hydrolysis of sunflower oil with the enzyme phospolipase A1 (Lecitase Ultra) and use mathematical modeling to obtain simulations of production processes of a diacylglycerol rich oil. Ultrasound generates emulsions of water and oil, thus enhancing the system s interfacial area, and producing higher reaction rates compared to conventional enzymatic processes. Sunflower oil partial hydrolysis was carried in a solvent free environment, in 4 hour periods, with temperatures varying from 30 to 50 °C, enzyme/substrate fractions between 0,6 and 4,0% (m/m) and a fixed water/oil fraction of 5% (m/m). with this goal in mind, experimental designs were developed. Results showed optimal reaction conditions on 40 °C and 1,7% (m/m). Subsequently, fixing the optimal parameters, water/oil fraction was evaluated between 2 and 10% (m/m) in a 12 hour period in order to obtain reaction kinetics. Applying a mathematical model to the kinetic curves it was possible to demonstrate that, for the tested fractions, the 2% water/oil ratio is the most favorable to the production of diacylglycerol, and the maximum quantity of this product is obtained at 27 minutes of reaction time.